Molecular determinants of allosteric modulation at the M1 muscarinic acetylcholine receptor - Abdul-Ridha, Alaa; López, Laura; Keov, Peter; Thal, David M.; Mistry, Shailesh N.; Sexton, Patrick M.; Lane, J. Robert; Canals, Meritxell; Christopoulos, Arthur (American Society for Biochemistry and Molecular Biology, 2014)
Background: BQCA is a selective allosteric modulator of the M1 mAChR. Results: Residues that govern BQCA activity were identified using mutagenesis and molecular modelling. Conclusion: BQCA likely occupies a pocket overlapping prototypical mAChR modulators and gains selectivity through coop- erativity with orthosteric ligands. Significance: Understanding the structural basis of BQCA function can provide insight into the design of more tailored allosteric ligands.